2009
DOI: 10.1002/pbc.21985
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with recurrent medulloblastoma or central nervous system germinoma treated with low dose continuous intravenous etoposide along with dose‐intensive chemotherapy followed by autologous hematopoietic stem cell rescue

Abstract: The strategy of low dose chronic exposure to a topoisomerase inhibitor along with ablative carboplatin and thiotepa with stem cell rescue showed promising survival outcomes in these relapsed patients. This treatment strategy deserves further evaluation in a larger group of high-risk or relapsed primary CNS tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The observation of the good response rate to metronomic [19,20] or conventional chemotherapy in this study suggests a future relapse study to contain an initial conventional chemotherapy, the utilization of all local treatment options and oral maintenance chemotherapy. Whether some specific group of patients will profit by an intensified chemotherapeutic approach, has to be further evaluated.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The observation of the good response rate to metronomic [19,20] or conventional chemotherapy in this study suggests a future relapse study to contain an initial conventional chemotherapy, the utilization of all local treatment options and oral maintenance chemotherapy. Whether some specific group of patients will profit by an intensified chemotherapeutic approach, has to be further evaluated.…”
Section: Discussionmentioning
confidence: 88%
“…Other authors had described a promising role of highdose chemotherapy in treating relapsed brain tumor patients [13][14][15][16][17][18][19][20][21][22][23]. The selectivity and heterogeneity of their patients and of their treatment should be considered.…”
Section: Discussionmentioning
confidence: 96%
“…The prognosis remains dismal for patients who experience disease progression. The expected 2‐year overall survival (OS) after disease progression is less than 25% . Management of these patients has been a challenge as there is no standard approach to salvage therapy …”
Section: Introductionmentioning
confidence: 99%
“…Two-year survival rates for relapsed medulloblastoma were reported to be below 20% (8). Recently, sequential cycles of dose-intensive chemotherapy or tandem transplantation have been tried in the treatment of chemo-sensitive high-risk or recurrent brain tumors, including recurrent medulloblastoma (9-11).…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate was reported as a broad range, 5-54%, by studies done in various different situations with regard to pre-transplant conventional chemotherapy, conditioning regimens, disease status prior to HDCT, and adjuvant therapy. Some studies did not separate recurrent medulloblastoma from high-risk medulloblastoma or other brain tumors types in their study group (8, 12). Grururangan et al (13) reported a 3-yr overall survival rate of 14% in recurrent medulloblastoma patients who underwent HDCT/ASCT and received no irradiation before relapse, while no survival was found in those who underwent HDCT/ASCT receiving irradiation before relapse and in those who did not undergo HDCT/ASCT and received only standard SC.…”
Section: Discussionmentioning
confidence: 99%